Widespread morphological parallelism in Korthalsella (Santalaceae, tribe Visceae): A molecular phylogenetic perspective. Issue 6 (20th December 2019) - Sultan, Amir; Robertson, Alastair W.; Callmander, Martin W.; Phillipson, Peter B.; Meyer, Jean‐Yves; Tate, Jennifer A.
Abstract: Korthalsella (Santalaceae, tribe Visceae) mistletoes are hemiparasitic plants that are widespread on islands and continental regions around the Indian and Pacific Oceans. In this study, we add key taxa to a previously generated dataset to produce a more inclusive phylogenetic analysis of the genus. The resulting nuclear ITS and plastid trnL‐F phylogenies reveal that the historical sectional classifications based on morphology are not supported. Instead, it appears that widespread morphological parallelism has occurred throughout Korthalsella . Geographical distribution seems to be a better indicator of phylogenetic relatedness as species found in the same geographic region, island or island group generally are more closely related to one another than species sharing similar morphological characters in other areas. We find greater support for recognition of species as local endemics rather than wide‐ranging taxa. Given these results, taxonomic changes that recognise previously described taxa are proposed, but other changes will require further study of broadly distributed taxa.